2004
DOI: 10.1200/jco.2004.02.139
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Adapted, Combined-Modality Therapy With VAMP/COP and Response-Based, Involved-Field Radiation for Unfavorable Pediatric Hodgkin's Disease

Abstract: Risk-adapted combined-modality therapy with VAMP/COP and response-based, involved-field radiation therapy results in an unsatisfactory outcome for pediatric patients with unfavorable presentations of Hodgkin's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 38 publications
2
44
1
4
Order By: Relevance
“…These results are similar to those described in the literature. (6)(7)(8)(9) Probabilities of OS and EFS were not statistically different when separated by staging as low or high risk (p = 0.402 and 0.969, respectively). This may be explained by the small sample size and because small variations in field strength and dose of radiotherapy treatment occurred as it was not adequately standardized, which may have interfered in the evaluation of EFS.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These results are similar to those described in the literature. (6)(7)(8)(9) Probabilities of OS and EFS were not statistically different when separated by staging as low or high risk (p = 0.402 and 0.969, respectively). This may be explained by the small sample size and because small variations in field strength and dose of radiotherapy treatment occurred as it was not adequately standardized, which may have interfered in the evaluation of EFS.…”
Section: Discussionmentioning
confidence: 97%
“…Hudson et al evaluated the use of COP with procarbazine in combination with VAMP for high-risk patients but the results were unsatisfactory. (6) Another scheme tested by Friedman et al (13) was the use of VEPA (vinblastine, etoposide, prednisone and doxorubicin) in combination with involved-field radiotherapy for advanced-disease patients (stage III or IV) and those with unfavorable risk factors and bulky tumors. The probabilities of OS and EFS at five years were 81.9% and 67.8%, respectively, with rates even lower for patients with advanced illness.…”
Section: Discussionmentioning
confidence: 99%
“…Among older patients with HL, it has been repeatedly demonstrated that the survival data in populationbased studies are poorer than those from clinical trials (Kennedy et al, 1985;Appleton et al, 1995;Clarke et al, 2001;Proctor et al, 2002;Jarrett et al, 2005). This effect is likely to be due, at least in part, to the exclusion of frailer elderly individuals from clinical NLPHD (n=7) cHL (n=48) NLPHD ( (Hudson et al, 1993(Hudson et al, , 2004Hutchinson et al, 1998;Friedmann et al, 2002). This may be another explanation of the differences between the present investigation and that of Yung co-workers; most of the patients in the latter study were registered at the time of recruitment to clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…[65] St. Jude/Stanford/Dana Farber'da 1993-2000 yılları arasında yüksek riskli hastalarda alkilleyici, antrasiklin ve radyoterapiye bağlı toksisitelerin azaltılması amaçlı risk adapte VAMP/COP'li (vinkristin, adriamisin, methotreksat, prednizolon, cyclofosfamid, vinkristin, prokarbazin) kemoterapi ve sonrasında uyguladıkları cevap ilişkili radyoterapinin değerlendirmelerinde geç rekürrenslerin çok olması nedeni ile çalışma erken sonlandırıldı. [66] Hastaların beş yıllık EFS'leri %75 olarak saptanarak, yazarlar yüksek riskli hastalarda alkilleyicilerin başarılı tedavide gerekli olduğunu vurguladılar. [66] Sonuç olarak 1990'lardan günümüze kadar çe-şitli gruplar tarafından yapılan çalışmalarda, erken evre HL'de %90'ların üzerinde olan sağ kalımın devamı sağlanırken toksisitenin azaltılması amaç-landı.…”
Section: Risk Grup Hasta Sayısı Sonuçunclassified
“…[66] Hastaların beş yıllık EFS'leri %75 olarak saptanarak, yazarlar yüksek riskli hastalarda alkilleyicilerin başarılı tedavide gerekli olduğunu vurguladılar. [66] Sonuç olarak 1990'lardan günümüze kadar çe-şitli gruplar tarafından yapılan çalışmalarda, erken evre HL'de %90'ların üzerinde olan sağ kalımın devamı sağlanırken toksisitenin azaltılması amaç-landı. Bu çalışmalarda çoklu ajan içeren kemoterapiler sıklıkla radyoterapi ile birlikte risk ve yanıta göre, bazı protokollerde de yan etkileri azaltma amaçlı cinsiyete göre verildi.…”
Section: Risk Grup Hasta Sayısı Sonuçunclassified